2021
DOI: 10.1038/s41598-020-79676-2
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructural deformation of high-stiffness spruce wood under tension

Abstract: Conifer wood is an exceptionally stiff and strong material when its cellulose microfibrils are well aligned. However, it is not well understood how the polymer components cellulose, hemicelluloses and lignin co-operate to resist tensile stress in wood. From X-ray scattering, neutron scattering and spectroscopic data, collected under tension and processed by novel methods, the ordered, disordered and hemicellulose-coated cellulose components comprising each microfibril were shown to stretch together and demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 69 publications
1
13
0
Order By: Relevance
“…Similar behavior has been found in other herbaceous fibers subjected to different load cycles [60][61][62]. On the other hand, the tensile mechanical behavior of wood sheets (thickness in microns) has also been studied [57,[63][64][65], as well as the influence of the microfibril angle [66] and the moisture content in very thin wood tissues subjected to longitudinal tensile creep [67]. Kamiyama et al investigated the effect of tensile loading on the angle of microfibrils in compression wood tissues, finding that they tend to align [68] and decrease the microfibril angle in the axial direction to the cell axis and load [69].…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…Similar behavior has been found in other herbaceous fibers subjected to different load cycles [60][61][62]. On the other hand, the tensile mechanical behavior of wood sheets (thickness in microns) has also been studied [57,[63][64][65], as well as the influence of the microfibril angle [66] and the moisture content in very thin wood tissues subjected to longitudinal tensile creep [67]. Kamiyama et al investigated the effect of tensile loading on the angle of microfibrils in compression wood tissues, finding that they tend to align [68] and decrease the microfibril angle in the axial direction to the cell axis and load [69].…”
Section: Introductionsupporting
confidence: 61%
“…In addition, this variability is also reflected in the variation in the microfibril angles [92], which is the main factor determining the mechanical properties [93]. Investigations using advanced spectroscopy techniques have reported that for wood having high microfibril angles subjected to tensile stress, the deformations are produced by polymer reorientation and sliding, while for wood with low microfibril angles, stretching of the disordered polymers is generated [65]. This implies that depending on the wood cell wall microfibril angles, the mechanical response, at the macroscopic level, will be greater or less depending on the case.…”
Section: Moduli Of Elasticity In Specimens Subjected To Tensile Creepmentioning
confidence: 99%
“…1a ) 11 . Elementary microfibrils frequently coalesce, forming large fibrils that often span across tens of nanometers 12 , 13 . Hemicelluloses, such as xylan, glucuronoxylan, arabinoxylan, and glucomannan, are highly variable in their monosaccharide composition and linkage pattern.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that µCt could be used to determine differences between earlywood and latewood shrinking and swelling in Picea abies wood samples [9,10]. More recently, a combination of X-ray scattering, neutron scattering and spectroscopic data was used to explore how the constituent polymers of wood cell wall interact to resist tension [12]. Dimensional change occurs due to a change in MC.…”
Section: Introductionmentioning
confidence: 99%